IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) MELALUI BUDAYA KUALITAS - Sri Hartini (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Total QualityManagement (TQM) is a new paradigm in running a business with the goal to maximize organizational competiveness through focuses on consumer satisfaction, all employee engagement, and sustainable improvement on quality of products, services, human, process and organizational environment.This research aims to determine the amount of effects by variables in the implementation of Total QualityManagementconsisting of:focuses on consumers, sustainable improvement, management commitment, training, employee empowering, performance comparison, and use of simultaneous statistic equipment on quality culture. The research method uses type of explanatoryresearch with quantitative approach because it tries to describe inter-variable correlation through hypothesis testing, meanwhile in general, the data used are in the form of number calculated by statistic test.Results of the research are (a) Simultaneously the variables in the implementation of TotalQuality Managementare able to describe the effects on the quality culture variable by 63,5%, meanwhile the remaining is described or influenced by other independent variables beyond the research model equation. Inter-variable correlation in the implementation of TotalQuality Management on the quality culture is quite strong (b) There are significant effects between variables in the implementation of Total QualityManagementconsisting of focuses on employee, management commitment, training, employee empowering, and use of statistic devices partially on quality culture variable, meanwhile the sustainable improvement and performance comparison do not influence significantly on quality culture variable. Thus, the second hypothesis of this research is rejected (c) The training variable provides dominant effects on the quality culture variable. Thus the third hypothesis of this research is rejected.